2017
DOI: 10.37358/rc.17.7.5722
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers with Low-grade Inflammation as Predictors of Thrombotic Events in Antiphospholipid Syndrome

Abstract: The study aimed to test the inflammation hypothesis in antiphospholipid syndrome (APS) by assessing biochemical markers of inflammation and platelet activation. Forty one patients with APS were compared to 40 controls. High-sensitivity C-reactive protein (hs-CRP) (as inflammatory biomarker), P-selectin and soluble CD40L (sCD40L) (as platelet activation markers) were measured by ELISA at enrolment and after 12 months follow-up. Serum hs-CRP, P-selectin and sCD40L levels were significantly higher in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…MAU is appreciated in all trials to be as a marker of generalized endothelial dysfunction and atherosclerosis, data consistent with the findings of the present study as it was more frequently diagnosed in RH patients with atherosclerotic disease as ischemic heart disease and peripheral vascular disease [25][26][27][28][29][30]. The relationship between CV comorbidities and the presence of MAU was investigated in the i-SEARCH study on 21,867 patients with high-risk hypertension.…”
Section: Resultssupporting
confidence: 87%
“…MAU is appreciated in all trials to be as a marker of generalized endothelial dysfunction and atherosclerosis, data consistent with the findings of the present study as it was more frequently diagnosed in RH patients with atherosclerotic disease as ischemic heart disease and peripheral vascular disease [25][26][27][28][29][30]. The relationship between CV comorbidities and the presence of MAU was investigated in the i-SEARCH study on 21,867 patients with high-risk hypertension.…”
Section: Resultssupporting
confidence: 87%
“…Tissue pretreatment with glutaraldehyde or formaldehyde are factors that promote the calcification of the extracellular matrix because they have a certain toxicity and do not allow to fix uniformly all the constituent elements of this matrix [6,[13][14][15][16]. Similar effects of glutaraldehyde and its derivatives have been described for medical devices also in other fields of interventional procedures [17,18] Various studies have hypothesized that the inflammatory and the immunological responses [19][20][21] could also play a role in the mineralization process of bioprosthetic tissues. Antibodies against donor valvular tissue components have been found in patients with structural deterioration of the bioprosthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Certain pregnant women are diagnosed with the socalled atypical preeclampsia (which does not involve hypertension or proteinuria) and their condition worsens unexpectedly [27]. The evaluation of the ratio of circulating angiogenic protein -sFlt-1/PlGF may contribute to differentiate preeclampsia manifested by hypertension or proteinuria from other conditions (systemic lupus erythematosus) [19,28,29]. The results obtained within this study have indicated a significant increase of the serum concentration corresponding to the sFLT-1 anti-angiogenic factor of more than 4 times for the PE group and of more than three times for the HTN group, compared to the control group.…”
Section: Results and Discussion Clinical And Laboratory Markersmentioning
confidence: 99%